Pengaruh Permainan Media Scrable Terhadap Pengetahuaan Keaksaraan Anak Usia 5-6 Tahun - Mardiyah, Taufiqah Ridha; Ira Reski Awalia; Reski Riswana Putri Ardi; Sitti Nurhidayah Ilyas; Herlina (Early Childhood Research Journal (ECRJ), 2025)
The introduction of letters to young children is often hindered by learning approaches that lack variety and engaging stimulation. This study aims to examine the effect of using Scrabble as a media game on improving letter recognition skills in children aged 5–6 years at TK Tunas Sejahtera. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of 22 children divided into an experimental group and a control group. Data collection techniques included observation, pre-test and post-test assessments, and documentation. The data were analyzed using descriptive statistics and the Wilcoxon Signed Ranks Test to measure the treatment’s effect. The results showed a significant improvement in the experimental group’s letter recognition ability, with an average post-test score of 22.27 compared to 10.36 in the pre-test. In comparison, the control group only improved from 8.36 to 17.27. Thus, Scrabble media games proved to be more effective. It can be concluded that Scrabble significantly enhances early childhood literacy, particularly in letter recognition. This research contributes to early literacy learning strategies and supports the use of creative educational media in early childhood education settings. The practical implication encourages teachers to integrate play-based learning in daily kindergarten activities.